2016
DOI: 10.5414/cp202467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel finasteride 0.25% topical solution on scalp and serum dihydrotestosterone in healthy men with androgenetic alopecia

Abstract: The novel finasteride 0.25% solution applied o.d. at the doses of 100 and 200 μL results in an appropriate inhibition of scalp DHT potentially minimizing the untoward sexual side-effects linked to a systemic DHT reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…19,20 Therefore, 0.25% finasteride solution has been suspected to be an optimal concentration in order to yield therapeutic benefits and minimize systemic drug absorption. From the recent studies, the ability of 0.25% finasteride solution in reducing plasma and scalp DHT levels was demonstrated to be equivalent to that of finasteride 1 mg daily while the plasma exposure was about 9-fold lower.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Therefore, 0.25% finasteride solution has been suspected to be an optimal concentration in order to yield therapeutic benefits and minimize systemic drug absorption. From the recent studies, the ability of 0.25% finasteride solution in reducing plasma and scalp DHT levels was demonstrated to be equivalent to that of finasteride 1 mg daily while the plasma exposure was about 9-fold lower.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that the route of administration could greatly influence the degree of toxicity, and oral administration was usually more risky than external use [54]. Because of that, it is worth trying to change the route of administration [55] or adjust the oral dosage [56] of finasteride, so as to reduce the toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid such side effects, many of the research groups have theorized and explored the strategy of administering finasteride directly to the scalp through topical delivery. 29,30 In fact, in a shortterm study topical finasteride solution (0.25%), with significantly lesser systemic exposure, generated almost same inhibitory effects on plasma DHT levels as that observed with 1 mg per day oral finasteride administration. 30 In a separate intermediate-term study, topical gel containing 1% finasteride was found to be as efficacious as 1 mg per day oral finasteride.…”
mentioning
confidence: 94%
“…29,30 In fact, in a shortterm study topical finasteride solution (0.25%), with significantly lesser systemic exposure, generated almost same inhibitory effects on plasma DHT levels as that observed with 1 mg per day oral finasteride administration. 30 In a separate intermediate-term study, topical gel containing 1% finasteride was found to be as efficacious as 1 mg per day oral finasteride. 31 In addition, the approach of delivering finasteride via topical route opens up several new possibilities such as combining topical minoxidil with topical finasteride which may improve overall efficacy, reduce potential health risks and provide superior patient compliance.…”
mentioning
confidence: 94%